TINJAUAN HUKUM EKONOMI SYARI’AH TERHADAP AKAD PERJANJIAN KERJA SAMA ANTARA PORTER DAN PT. KAI - Asril, Andi; Harun, Muhamad; Nilawati, Nilawati (Program Studi Muamalah Fakultas Syariah dan Hukum, 2024)
The cooperative relationship between the company and the workers still leaves serious problems regarding the rights and obligations of each party, as well as what happens in the cooperative relationship between the porter and the company PT. KAI at Palembang Kertapati Station. This study aims to determine the mechanism of the work relationship between the porter and PT. KAI at Palembang Kertapati Station, knowing the role of porters in improving the service quality of PT. KAI at Palembang Kertapati Station, and knowing the sharia economic law review of the cooperation agreement between the porter and PT. KAI at Palembang Kertapati Station. The method used in this research is to use a qualitative approach. This type of research is field research. Sources of data used are primary data sources and secondary data sources. Respondents or informants in this study are people who have knowledge of the work of porters at Palembang Kertapati Station, and some of the porters themselves. Data collection techniques are carried out through observation, interview, and documentation techniques. The results of the analysis in the discussion can be concluded from several points, namely: First, the working relationship between the porter and PT. KAI at Palembang Kertapati Station is a volunteer worker at PT. KAI that works at Palembang Kertapati Station with a permit and coordination mechanism at the Head of Kertapati Station in Palembang. Second, the role of porters in improving the service quality of PT. KAI at Palembang Kertapati Station is to fulfill the vision of PT. KAI. And third, a review of sharia economic law on the cooperation agreement that if viewed based on the contract, the work agreement or syirkah (in Islamic view) that occurs between the porter and PT. KAI is a syirkah 'abdan / syirkah' charity, and if seen according to thecontract ijarah, even though in the working relationship between the porter and PT. KAI at Palembang Kertapati Station according to PT. KAI that porter is not part of PT. KAI and also not part of Palembang Kertapati Station, but the wages earned by porters are directly from passengers who use their services on the terms of the rates set by PT. KAI.